(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
It was revealed, that the complex of scientific and practical problems are related to the definition of cross-border nature of the market of tourist and recreational services and remains under-researched in the foreign and domestic scientific literature. There is also reveals the social economic contentof tourist and recreational services, cross-border nature of the author’s definition of the market of tourist and recreational services. It is very important and effective to use a systematic approach for exploration of cross-border market of tourist and recreational services.These principles will reveal the essence of cross-border market of tourist and recreational services as a major social and economic system with different parameters, what is the part of another system – the cross-border region economy. Defined subjects and objects of cross-border market tourist and recreational services as a complex socio-economic system.Subjects and objects of cross-border market of tourist and recreational services are described as a complex of socio-economic system.